2012
DOI: 10.1039/c1jm14874e
|View full text |Cite
|
Sign up to set email alerts
|

ZnFe2O4: Rapid and sub-100 °C synthesis and anneal-tuned magnetic properties

Abstract: Nanocrystalline zinc ferrite (ZFO) has been synthesized from metal acetylacetonates by microwave irradiation for 5 min in the presence of a surfactant. The as-prepared material is ZFO and has been subjected in air to conventional furnace annealing and to rapid annealing at different temperatures. Both annealing protocols lead to well-crystallized ZFO, with crystallite sizes in the range $8-20 nm, which is ferrimagnetic, even at room temperature, with magnetization attaining saturation. While the magnetization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…Generally, the synthesis of a crystalline ceramic such as ZnAl 2 O 4 requires high temperatures and/or long durations. The present work demonstrates that microwave irradiation can be used to synthesize fine‐grained refractory oxides at temperatures as low as 220°C relatively quickly (40‐60 minutes), the rapidity stemming from the dielectric heating at the molecular level that leads to uniform heating and high local temperatures . Considering that the material is a ceramic, 220°C is quite low (compared to co‐precipitation method) for synthesizing crystalline material and much faster compared to other methods.…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Generally, the synthesis of a crystalline ceramic such as ZnAl 2 O 4 requires high temperatures and/or long durations. The present work demonstrates that microwave irradiation can be used to synthesize fine‐grained refractory oxides at temperatures as low as 220°C relatively quickly (40‐60 minutes), the rapidity stemming from the dielectric heating at the molecular level that leads to uniform heating and high local temperatures . Considering that the material is a ceramic, 220°C is quite low (compared to co‐precipitation method) for synthesizing crystalline material and much faster compared to other methods.…”
Section: Resultsmentioning
confidence: 79%
“…Synthesis of ceramics using this method was first attempted by Komarneni et al This technique is advantageous over conventional methods because of: (i) high reaction rates; (ii) excellent control over reactions; (iii) higher yields; and (iv) improved reproducibility . Though there are a few reports describing the microwave synthesis of spinel oxides, the processes described are either lengthy or highly pH‐sensitive. Further, the synthesis of transition metal‐doped ZnAl 2 O 4 nanoparticles using this method has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, toxic solvents and additives should be avoided. In this regard, microwave chemistry is promising and has recently been applied to the synthesis of ferrite nanoparticles, too [7]. It is important to note that microwave irradiation provides a selective heating tool, which means that substances with different microwave absorbing properties will be heated unequally.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our ongoing research work on microwave assisted synthesis of nano materials [11,12] we have found that, nano-crystalline metal oxides have attracted considerable attention of synthetic and medicinal chemists because of their high catalytic activity and reusability [13][14][15][16][17][18][19][20][21][22][23][24][25]. Zinc oxide is an inexpensive, moisture stable, reusable, commercially available and is non-toxic, insoluble in polar as well as non-polar solvents [26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%